Spatially Axial Boron Coordinated Single‐Atom Nanozymes with Boosted Multi‐Enzymatic Performances for Periodontitis Treatment - Liu, Wendong; Shi, Enyu; Wu, Hao; Liang, Yanjie; Chen, Mingyue; Zhang, Hongyan; Zhang, Ruizhong; Li, Xiyan; Wang, Yinsong; Zhang, Libing (Advanced functional materials, 2024)
Single‐atom nanozymes (SAzymes) have made significant strides in antibacterial treatment but fall short as natural enzyme and drug replacements due to limited catalytic performance. Here, a rational strategy is presented for incorporating spatially axial boron (B) ligands to effectively modulate the local coordination environment of planar Fe─N4 motifs (Fe─B/N─C SAzymes). With electronic modulation, the Fe─B/N─C SAzymes exhibit significantly enhanced oxidase‐, peroxidase‐, and catalase‐like activities. Theoretical calculations highlight that the spatially axial B ligands effectively adjust the charge distribution around the planar Fe─N4 active center, which facilitates the heterolysis of H2O2 and the desorption of O2, resulting in accelerated H2O2 decomposition. Furthermore, the intrinsic photothermal effect of Fe─B/N─C SAzymes enhances multienzyme‐like activities, rapidly generating abundant reactive oxygen species (ROS), and achieving chemodynamic/photothermal synergistic therapy for impressive disinfection against periodontal‐related pathogenic bacteria. These findings offer a distinctive viewpoint for optimizing the local coordination environment of SAzymes with axial ligand to enhance their catalytic performance and effectiveness in periodontitis therapy. A rational strategy is developed to enhance the multienzymatic performance of SAzymes by spatially axial boron ligands, which effectively modulate the local coordination environment of planar Fe─N4 motifs (Fe─B/N─C). The photothermal effect of Fe─B/N─C SAzymes accelerates the multi‐enzyme‐like activities for the rapid generation of abundant reactive oxygen species (ROS) and O2, showcasing impressive disinfection efficacy against periodontal‐related pathogenic bacteria.